The Konsep Ideal Penyitaan Dalam Sistem Peradilan Pidana - Syam, Asmadi; Din, Mohd; Safliana, Devi (The Prosecutor Law Review, 2025)
The basic concept of confiscation still refers to Article 38 Paragraph (1) of the Criminal Procedure Code and can only be carried out by investigators. In its development, this concept is no longer relevant to maintain, because it is known that in handling cases many items/objects are found after the prosecution process, so for its validity an acquisition method is needed so that it can be considered in the judge's decision. This research aims to elaborate on the authority of confiscation at the prosecution process and its juridical impact as well as the ideal concept of confiscation. The research method used is normative legal research with secondary data consisting of primary, subsidiary and tertiary legal materials. The research results show that the authority of confiscation at the prosecution process is still contradicted each other with the formal legality of the Criminal Procedure Code. The ideal concept of confiscation must start from a change in the definition of confiscation, which is known as an action by law enforcement officials to take control of movable and immovable property, including electronic devices/electronic information systems for the purposes of proving a criminal act at every level of case handling, as well as the concept of confiscating collateral as in civil law. adopted as an effort to guarantee the return of state losses.